Histomorphological Differences Between Right and Left Sided Colon Cancers - ., Danyal (International Journal of Pathology, 2022)
Introduction: Colorectal cancer (CRC) is third most common cancers of the world. Right and left sided colorectal cancers are different with respect to clinical, histological, and genetic aspects.Objectives: The objective of the study was to analyze and compare right and left sided colorectal cancers regarding different clinic-pathologic parameters like grade, subtypes, stage of colorectal carcinoma.Materials and Methods: A retrospective cross sectional comparative (Analytical) study was conducted at Department of Pathology, Peshawar Medical College during January 2022. Study included consecutive cases of CRC received at PMC Labs, Histopathology section from 2011 – 2021. Hematoxylin and Eosin slides were re-examined for Tumor Subtype, Grading, AJCC staging, Vascular Invasion, and Perineural Invasion. Cases do not have all the study para meters were excluded. Statistical analysis was performed using SPSS version 20.0. Chi Square test and Fisher’s exact tests were performed for categorical variables.Results: Left sided colorectal cancer cases were more common than left sided colorectal cancer cases. Mean age for right sided Colorectal Cancers (RSCRC) was 52.88 ±16.54 years and 44.03 ±13.81 for left sided colorectal cancers (LSCRC). Male to female ratio was 1.7:1 and 2:1 for Right and Left sided colorectal cancers respectively. Most common site for right sided CRCs was Cecum and that for left sided CRCs was Sigmoid Colon.Adenocarcinoma (Mucinous type) was significantly associated with RSCCs although Adenocarcinoma NOS was the predominant Subtype for both sides. Right Sided CRCs exhibited greater (average diameter) tumor size, advanced stage and more lymph nodes harvest.No difference was identified between right and left side regarding Tumor perforation, N stage, Tumor differentiation, lympho-vascular invasion and Perineural invasion.Conclusion: Our study concluded that RSCC and LSCRC are quite diverse entities. RSCC is associated with older age, increased tumor size, Advanced T stage, Mucinous Subtype, and more lymph node harvest.